Gambaran pola konsumsi makanan pada ibu hamil di kota Manado - Narasiang, Bezaliel R.; Mayulu, Nelly; Kawengian, Shirley (Universitas Sam Ratulangi, 2016)
Abstract: Pregnancy is a critical time or a golden period of the brief human growth and development time, a part of the Window of Opportunity, which affects the maternal and fetal health. Throughout the first phase of pregnancy, pregnant women need more food intake, accurate eating pattern, and also a balanced macronutrient intake. An adequate intake of food is very important to support the physical health and development of fetal mental health also decrease the risk of pregnancy complications. This study was aimed to obtain the description of food consumption pattern in pregnant women in Manado. This was a descriptive study with a cross sectional design using Food Frequency Questionnaire (FFQ) to obtain data of pregnant women in 5 public health centers in Manado from September to October 2016. Based on the FFQ data given by 181 respondents, the consumption of pregnant women in Manado was as follows: carbohydrate 159.97g/day, protein 79.15g/day, and fat 124.74g/ day. The most common foods consumed by the pregnant women were rice (carbohydrate), saltwater fish (protein), and coconut oil (fat). Meanwhile, chicken was rarely consumed (81.22%) and eel was never consumed (100%). Conclusion: Pregnant women in Manado had a food pattern that was lack in carbohydrate and high in fat according to pregnant women Recommended Dietary Allowances (RDA) in Indonesia.Keywords: pregnant women, food pattern, food frequency questionnaireÂ Abstrak: Kehamilan merupakan masa kritis atau masa emas tumbuh kembang manusia yang singkat, bagian dari Window of Opportunity, yang memengaruhi kesehatan ibu dan janin. Sepanjang tahap awal kehamilan, ibu hamil membutuhkan konsumsi makanan yang lebih dari semula, pola makanan yang tepat, juga asupan makronutrien yang seimbang. Pola asupan makanan yang adekuat sangat penting untuk menunjang kesehatan fisik, perkembangan mental janin, dan menurunkan komplikasi kehamilan. Penelitian ini bertujuan untuk mendapatkan gambaran umum pola konsumsi makanan pada ibu hamil di Kota Manado. Jenis penelitian ialah deskriptif dengan desain potong lintang menggunakan Food Frequency Questionnaire (FFQ) pada ibu hamil di 5 puskesmas di Kota Manado selama bulan September-Oktober 2016. Berdasarkan perolehan data FFQ dari 181 responden, didapatkan bahwa konsumsi karbohidrat ibu hamil di Kota Manado sebanyak 159,97gr/hari, protein sebanyak 79,15gr/hari, dan lemak sebanyak 124,74gr/hari. Makanan tersering dan terbanyak yang dikonsumsi ialah beras (karbohidrat), ikan air laut (protein), dan minyak kelapa (lemak). Ayam merupakan makanan yang jarang dikonsumsi (81,22%) dan belut merupakan makanan yang tidak pernah dikonsumsi ibu hamil (100%). Simpulan: Ibu hamil di Kota Manado memiliki pola makan yang rendah karbohidrat dan tinggi lemak berdasarkan AKG ibu hamil di Indonesia. Kata kunci: ibu hamil, pola makan, food frequency questionnaire